2020
DOI: 10.1101/2020.11.05.20226381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in physical activity, sitting and sleep across the COVID-19 national lockdown period in Scotland

Abstract: We examine the impact of the COVID-19 outbreak and concomitant restrictions (i.e. lockdown) on 24-hour movement behaviors (i.e. physical activity, sitting, sleep) in a purposive sample of people (n=3230) reporting change recruited on-line. Participants' self-reported time spent in moderate-to-vigorous physical activity (MVPA), walking, sitting and sleep prior to lockdown (T1), during the first national lockdown (T2) and as restrictions initially started to ease (T3). For each 24-hour movement behavior, categor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…This study is the first to examine the heterogeneity in longitudinal changes in physical activity during the COVID-19 pandemic. Building on recent longitudinal studies, which reported a general decline in physical activity at the start of the pandemic, [10][11][12][13][14][15]25 our analyses identified six unique classes of growth trajectories of physical activity. Three of these classes were stable, showing little change over time, including the inactive (11.6%), the fairly active (22.2%) and the highly active (28.6%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is the first to examine the heterogeneity in longitudinal changes in physical activity during the COVID-19 pandemic. Building on recent longitudinal studies, which reported a general decline in physical activity at the start of the pandemic, [10][11][12][13][14][15]25 our analyses identified six unique classes of growth trajectories of physical activity. Three of these classes were stable, showing little change over time, including the inactive (11.6%), the fairly active (22.2%) and the highly active (28.6%).…”
Section: Discussionmentioning
confidence: 99%
“…These differing trajectories may explain the inconsistent findings to date from longitudinal studies testing whether physical activity returned to pre-lockdown levels with the easing of restrictions in the UK. 10,11,14,15 This study further examined sociodemographic and health-related predictors of physical activity growth trajectories. When comparing the three stable classes (inactive, fairly active, and highly active; LC1-3), we found no gender, ethnic, or urban/rural differences between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the process of Janssen et al (2020) we categorised the changes in sleep, sitting, walking and MVPA that participants had experienced from pre-lockdown to lockdown as either ‘positive change’, ‘negative change’, ‘no change’ and ‘already optimal’ based on previously reported categorizations for levels of physical activity (Ekelund et al, 2016), sitting (Stamatakis et al, 2019) and sleep (the National Sleep Foundation’s Sleep Duration Recommendations). As our interest is in cross-domain positive change we created an additive cross-domain positive change score as primary dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Positive changes have also been observed in health-related behaviors, with Janssen et al (2020) reporting that although levels of sedentary behavior increased during lockdown, levels of moderate to vigorous activity increased and participants reported sleeping longer at night. It was also noted that participants who changed one behavior positively were also more likely to report a positive change in another demonstrating an important clustering in positive behavior change.…”
mentioning
confidence: 98%